233 COGNITIVE OUTCOMES AFTER A FIRST EPISODE OF DELIRIUM IN HOSPITAL – RESULTS FROM AN ADVANCED NURSE PRACTITIONER DELIRIUM CLINIC. (25th October 2022) - Ryan, S; Sayers, K; King, L; Maher, J; O'Reilly, A; Donnellan, C; Pillay, I
Abstract: Background: Cognitive outcomes for frail older adult inpatients with a first episode of Delirium are unknown. Aim : To determine cognitive outcomes of frail older inpatients after a first episode of Delirium. Methods: Consecutive frail older inpatients with a 4AT score >/= 4, without a previous history of cognitive impairment, over a 12-month period (January to December 2021) were invited for formal cognitive assessment 8-12 weeks after their delirium occurred. Collateral history, medication review, Addenbrookes (ACE III), bloods and CT brain were undertaken. Data was prospectively entered onto Excel and analysed using descriptive statistics. Results: Fifty-one patients with a mean age of 82 years (SD=6) were referred to the Advanced Nurse Practitioner (ANP) Delirium Clinic. Median Clinical Frailty Score (CFS) was 6 with a male: female ratio of 1:2. Forty- seven percent (n=24) attended; 35 % (n-18) did not attend; 18 % (n=9) died prior to assessment. The ratio of male to female attendees was 1: 2.4. There was no difference in CFS or age between attenders and non-attenders. Thirty-three percent (n=8) of patients who attended had potentially reversible causes (high anti-cholinergic burden, folate deficiency, sleep disorder) of cognitive impairment requiring intervention. Sixty-seven percent (n=16) were diagnosed with dementia at the Delirium Clinic; 16.6% (n=4) were diagnosed with Mild Cognitive Impairment; 4% (n=1) had a resolved delirium; 8% (n=2) were referred to consultant Memory Clinic and one patient remained too unwell to assess. The median ACE III score of patients diagnosed with dementia was 54/100 (SD = 18). Conclusion: Pro-active follow up of patients with a first episode of Delirium led to early diagnosis of dementia and mild cognitive impairment with supportive interventions. Earlier ANP intervention, during the acute phase of delirium, has been introduced in order to improve clinic attendance.